Perancangan Program Inventori Berarsitektur Three Tier Berorientasi Objek Menggunakan Java Pada PT. Krama Yudha Ratu Motor Jakarta - Rusdi Permana; Taufik Baidawi; Lestari Yusuf (JURNAL TEKNIK KOMPUTER AMIK BSI, 2017)
Fluctuations of production volume at PT. Krama Yudha Ratu Motor  which can increase and decrease every month, can inflict an inventory system problem of its own in Part Control Local. The Slowness in the development of computer technology, which is now already integrated to each other, makes it difficult for Part Control Local to monitor the activities of spare parts inventory. This program is designed to help Part Control Local monitoring inventory activities in form of a new system with application programs created using Java programming language that has a three tier architecture and utilizes swing components as an interaction between the user and the system. Application Inventory that has been made generates a new system  which can help Part Control Local to monitor spare parts at the warehouse where the user application can connect to the inventory information data center of Part Control Local  so the recording process of inventory activites becomes more well-structured